Prevalence and Antibiotic Resistance of Salmonella Serotypes in Chicken Meat of Ardabil, Northwestern Iran - Aidin Azizpour (Iranian Journal of Medical Microbiology, 2021)
Background and Objective: Salmonellosis is one of the most important zoonotic diseases; most of the infections caused by the consumption of contaminated food is caused by this bacterium. During the last decades, the resistance of Salmonella isolates to conventional antibiotics has increased, which is a global health problem. The objective of this study was to investigate Salmonella serotypes in chicken meat and their antibiotic resistance regarding ten commonly used antibiotics in Iran. Materials and Methods: A totsl of 100 chicken meat samples were collected randomly from meat supply and distribution centers of Ardabil City. After cultivation and isolation of Salmonella, its colonies were examined by serological and PCR methods. Finally, PCR confirmatory test was also used for confirmation of Salmonella Typhimurium. Antibiotic resistance of the isolates was determined by Kirby Bauer method. Results: Of the 100 samples, 6 isolates of Salmonella (6%) were obtained of which, 3 isolates (50%) belonged to Salmonella infantis, 1 isolate (16.6%) to Salmonella enteritidis, 1 isolate (16.6%) to Salmonella Typhimurium and 1 isolate (16.6%) to Salmonella thompson. More than 60% of the isolates were resistant to seven antibiotics. The highest drug resistance rates were against ampicillin (83.3%), sulfadiazine+trimethoprim (83.3%), chloramphenicol (83.3%), co-trimoxazole (66.7%), amikacin (66.7%), tetracycline (66.7%), doxycycline (66.7%) and florphenicol (16.7%). No resistance was observed against enrofloxacin and ciprofloxacin. Conclusions: The results of this study indicated the dominant serotype of Salmonella which is Salmonella infantis. The results showed that Salmonella isolates are resistant to the majority of the ten antimicrobial agents commonly used in the livestock and poultry industry, which is important for public health.